Extreme ionospheric ion energization and electron heating in Alfvén waves in the storm time inner magnetosphere. Issue 24 (31st December 2015) - Chaston, C. C.; Bonnell, J. W.; Wygant, J. R.; Kletzing, C. A.; Reeves, G. D.; Gerrard, A.; Lanzerotti, L.; Smith, C. W.
Abstract: We report measurements of energized outflowing/bouncing ionospheric ions and heated electrons in the inner magnetosphere during a geomagnetic storm. The ions arrive in the equatorial plane with pitch angles that increase with energy over a range from tens of eV to > 50 keV while the electrons are field aligned up to 1 keV. These particle distributions are observed during intervals of broadband low‐frequency electromagnetic field fluctuations consistent with a Doppler‐shifted spectrum of kinetic Alfvén waves and kinetic field line resonances. The fluctuations extend from L ≈ 3 out to the apogee of the Van Allen Probes spacecraft at L ≈ 6.5. They thereby span most of the L shell range occupied by the ring current. These measurements suggest a model for ionospheric ion outflow and energization driven by dispersive Alfvén waves that may account for the large storm time contribution of ionospheric ions to magnetospheric energy density. Key Points: Dispersive Alfven waves may pump up ion energy density in the inner magnetosphere Dispersive Alfven waves accelerate ionospheric ions in the inner magnetosphere Dispersive Alfven waves drive field‐aligned electron heating/acceleration in the inner magnetosphere